Reduced serum zinc levels while improving growth of underweight school children in trial of zinc-fortified milk in Indonesia - Endang Dewi Lestari; Lilisianawati Lilisianawati; Saptawati Bardosono; Leilani Lestarina; Harsono Salimo (Indonesian Pediatric Society, 2012)
Background Most children in low-income countries haveinadequate dietary zinc. The study was aimed to demonstrate theeffect of iron-zinc fortified milk in improving zinc status amongunderweight school children in Indonesia.Objective To evaluate the effects of milk fortification with zinc onserum zinc levels in underweight Indonesian school children.Methods A double-blind, randomized, controlled, communitybasedstudy was conducted on 426 underweight children aged 7to 9 years in several low economic income level elementary schoolsin Jakarta and Solo. Subjects were randomly allocated to receiveeither zinc-fortified milk (n= 217) or standard milk (n=209) for6 months. The fortified milk provided an 2.38 mg zinc per dayand the standard milk provided 0.88 mg zinc per day.Results Among underweight children, the prevalence of stuntingwith a height-for-age z-score < - 2.0 SD was 39.7%. Almost allsubjects (98%) had zinc intake ofless than 60% of the Indonesianrecommended daily allowance (RDA) for that particular agegroup. After receiving the milk intervention, mean serum zincconcentration declined significantly in both groups (from 13 .50Â±3.05 Î¼mol/Lat baseline to 10.59Â±1.93 Î¼mol/L, P< 0.05), butgrowth parameters (weight and height) improved.Conclusion Reduced mean serum zinc levels were observed inchildren who received standard milk, as well as those who receivedzinc-fortified milk. These reduction in serum zinc levels may be apart of homeostatic control mechanim for improving the negativezinc balance in zinc pools, as a negative effect on linear growthwas not observed. Larger clinical trials of adequate sample sizeneed to be conducted in order to provide better understandingon zinc regulation among underweight school children. [Paediatrlndones. 2012;52:118-24).